Leadership Styles of Public Schools Principals in the City of Hail in the Kingdom of Saudi Arabia - Alshammari, Fahad Husain (Journal of Educational and Psychological Sciences, 2021)
This study aimed to: Identify the leadership style prevailing among public school principals in Hail from the teachers ’point of view, and to reveal the statistical significance of the differences in the estimates of the study sample individuals of the leadership style prevailing among school principals, which may due to variables of (educational stage, number of years of experience, and specialization). The researcher used the descriptive method, and prepared a questionnaire consisting of (24) statements distributed to (3) dimensions, which are: Democratic style, authoritarian style and chaotic style. The current study population included all the teachers of public education schools in Hail, who numbered (9390) teachers. The questionnaire was applied to a random sample of (296) teachers. The study found a set of results, the most important of which are: The prevailing leadership style among school principals is the democratic style, followed by the authoritarian style, and then the chaotic style. Where the democratic style obtained a mean (4.18) and a high degree of approval from the study sample, while the domineering style obtained a mean (1.83) and a low degree of approval from the study sample, and the chaotic style obtained an average (1.73) and a low degree of approval. Very members of the study sample. The results also showed that there are statistically significant differences in the degree of the study sample’s estimates of the leadership style prevailing among school principals due to the variable of years of experience, while there are no statistically significant differences in the degree of the study sample’s estimates of the leadership style prevailing among school principals due to the variables of the educational stage or specialization. In light of these results, the researcher recommended organizing training courses for school principals to enlighten them about the modern trends in educational leadership, and urged school principals to follow the democratic style of administration.
Keywords: Leadership Styles; Public Schools Principals; the City of Hail